2014
DOI: 10.1097/dcc.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Critical-Care Pain Observation Tool in Adult Critically Ill Patients

Abstract: The CPOT is an acceptable behavioral pain assessment scale for use in the general critical care patient population and is more appropriate for use with adults than the FLACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 16 publications
2
32
1
Order By: Relevance
“…The vast majority of patients included in this study were intubated and awake, with RASS scores between À1 to +1 despite severe illness. 24,33,[35][36][37] G elinas et al concluded in their study that patients' bodily behavior was more visible and obvious in the conscious patient group compared to the sedated group. [36][37][38] We did not find any correlation between physiologic indicators and CPOT scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of patients included in this study were intubated and awake, with RASS scores between À1 to +1 despite severe illness. 24,33,[35][36][37] G elinas et al concluded in their study that patients' bodily behavior was more visible and obvious in the conscious patient group compared to the sedated group. [36][37][38] We did not find any correlation between physiologic indicators and CPOT scores.…”
Section: Discussionmentioning
confidence: 99%
“…24 The patients' severe illness and treatment can enable their capability to self-report pain even though they are not sedated. 24,[31][32][33][34][35][36][37][38][39] International guidelines recommend valid pain assessment tools, but emphasize the importance of proper validation and testing before implementing the assessment method in clinical practice. 13,25 Therefore, validated pain assessment tools have been developed.…”
Section: Editorial Commentmentioning
confidence: 99%
“…As neurosurgical and delirium populations are frequently encountered in critical care and palliative care patient populations, these studies should be replicated removing the confounder of language. Numerous investigators have conducted studies comparing the CPOT to other behavioral pain assessment tools in intensive care units of various types 18,27,46-48 . In most studies, the CPOT performed as well or better than other tools although it did not perform well in the burn population which could self-report 49 .…”
Section: Review Of Selected Pain Assessment Toolsmentioning
confidence: 99%
“…Based on the combined sample data, the authors suggested that the FLACC might be useful across populations and settings. Two studies, one comparing the FLACC to the CPOT and Nonverbal Pain Scale (see below) 54 , and the other comparing the FLACC to the CPOT 46 inexplicably omitted data on the FLACC and focused almost exclusively on the CPOT, thus adding little to knowledge about the FLACC. Although Buttes et al 46 noted that the two study data collectors thought the CPOT was more appropriate for adults than the FLACC, they did not present an explanation to support this statement.…”
Section: Review Of Selected Pain Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation